Planning, Conducting and Reporting the Review of Employability using Data Mining and Predictive Analysis - Tan, KianLam; Azziaty Abdul Rahman, Nor; Lim, ChenKim (International Journal of Engineering and Technology, 2018)
A new research involves the collection and analysis of several research papers and it requires systematic methods of identifying the gaps and generating reliable evidence as a whole. Research questions can be drawn through the results of a systematic study that summarizes the overall research thoroughly. This paper aims giving an exposure on the systematic review used in the study of graduates' employability using data mining techniques and predictive analysis. Three main processes; (i) planning, (ii) conducting and (iii) reporting the review have been conducted to answer the research questions on predictive analysis conducted on the problem of employability among the fresh graduates. The methods of the review and specifies the research questions described through a review protocol involving three main databases; (i) Scopus, (ii) ScienceDirect and (iii) Web of Science. A total of 120 journal articles are classified into three main categories through taxonomy analysis. The results of the study are discussed in three main aspects; (i) challenges, (ii) motivations and (iii) recommendations while the research interest of the analysis results is critically formulated under critical review.Â